Avaliação da influência da agitação no tratamento anaeróbio por leito fixo de manipueira - Almeida, Crislene Barbosa de [UNESP]; Bueno, Gisele Ferreira [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (My University, 2010)
The objective of this work was to evaluate the stir influence in a continuous fixed bed anaerobic system for “manipueira” treatment (wastewater from cassava flour production). For so much, two glass reactors were used, with 1.55L useful volume and plastic rings as support. The reactors possessed intermittent upflow and HRT equal to 5 days. The pH, COD, alkalinity and acidity determinations were accomplished according to APHA (1995). The feed concentration varied from 700 to 2000 mg. L-1 COD. The reactor without agitation obtained COD reductions varying from 89.4 to 96.2% while the efficiency of the stirred reactor varied from 70.8 to 93.6%. The pH, in each reactor, varied from 7.5 to 8.0 and a relationship medium acidity/alkalinity of 0.18 for the reactor without agitation and of 0.25 for the agitated one, values considered ideals for this treatment type, according to the literature. Like this, it was concluded not to be advantageous the use of the anaerobic treatment for this agitation type, because, besides the energy consumed by an agitator, it was verified that this treatment is less efficient in relation to COD reductions.

O objetivo do trabalho foi avaliar a influência da agitação em um sistema anaeróbio contínuo de leito fixo para o tratamento de manipueira (água residuária da fabricação de farinha de mandioca). Para tanto, foram utilizados dois reatores de vidro, volume útil de 1,55L e anéis de plástico como suporte. Os reatores possuíam fluxo ascendente intermitente e TRH de 5 dias. As determinações de pH, DQO, alcalinidade e acidez foram realizadas conforme APHA (1995). A concentração de alimentação variou de 700 a 2000 mg.L-1 DQO variando de 89,4 a 96,2% enquanto que a eficiência do reator agitado variou de 70,8 a 93,6%. O pH, em cada reator, variou de 7,5 a 8,0 e uma relação acidez/alcalinidade média de 0,18 para o reator sem agitação e de 0,25 para o agitado, sendo estes valores considerados ideais para este tipo de tratamento, conforme literatura. Assim, conclui-se não ser vantajoso o emprego do tratamento anaeróbio por este tipo de agitação, pois, além da energia consumida por um agitador, verifica-se que este tratamento mostrou-se menos eficiente quanto às reduções de DQO.
Evaluation of the stir influence in a continuous fixed bed anaerobic system for “manipueira” treatment
Keywords: manipueira; leito fixo; tratamento anaeróbio; cassava wastewater; fixed bed; anaerobic treatment